Screens are a game changer: How environments influence social capital in the digital era - Park, Giyoung (Cogent social sciences, 2017)
Accumulated social interactions shape social capital—that is, resources available through social ties—that benefits individuals, groups, and society at large. Personal electronic communication media and devices, termed herein screens, are a new type of environment interacting with other environments within an ecological system. Environments influence interpersonal communication in and across settings; yet little is known about the influence of context wherein virtual and in-person social interactions occur. After overviewing the characteristics of the screens, the present paper examines how four geographical contexts—middle-class suburbs, impoverished neighborhoods, urban neighborhoods, and college communities—can influence on the relationship between the screen and local social capital. Lastly, this paper discusses environmental design implications for reducing screen usage that harms social capital.